2010
DOI: 10.1001/archneurol.2010.179
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis-Independent Alzheimer Disease Biomarker Signature in Cognitively Normal Elderly People

Abstract: To identify biomarker patterns typical for Alzheimer disease (AD) in an independent, unsupervised way, without using information on the clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
255
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(275 citation statements)
references
References 25 publications
(42 reference statements)
16
255
0
2
Order By: Relevance
“…The plots per subgroup show that EC variability against test score is lower in e4 carriers. This indicates differences in brain network organization between carriers and noncarriers that make the brain more vulnerable to AD‐related pathology (De Meyer et al., 2010; Evans et al., 2014; Mintun et al., 2006; Sperling et al., 2011). In an important way, this does not lead to decreased cognitive decline or visuoperceptual performance.…”
Section: Discussionmentioning
confidence: 99%
“…The plots per subgroup show that EC variability against test score is lower in e4 carriers. This indicates differences in brain network organization between carriers and noncarriers that make the brain more vulnerable to AD‐related pathology (De Meyer et al., 2010; Evans et al., 2014; Mintun et al., 2006; Sperling et al., 2011). In an important way, this does not lead to decreased cognitive decline or visuoperceptual performance.…”
Section: Discussionmentioning
confidence: 99%
“…These CSF biomarkers are also prognosis markers since a recent prospective study conduct on 150 AD patients for 5 years revealed that extreme CSF biomarkers levels (high Ttau and P-tau 181 and low A 42 ) are associated with more aggressive diseases leading to an earlier death (Wallin, Blennow et al 2010). Recently, a clinical study of the Alzheimer Disease Neuroimaging Initiative Project has detected an Alzheimer disease signature in the CSF levels of, Aß 42 T-tau and P-tau181 in more than one third of cognitively normal subjects (De Meyer, Shapiro et al 2010). This finding suggests that this CSF signature is present and detectable early during the neurodegenerative process.…”
Section: Which Csf Biochemical Markers Might Allow Us To Detect Alzhementioning
confidence: 99%
“…Neuroimaging and CSF parameters increasingly came into use especially in the first decade of the new millennium leading to newly proposed research criteria finally being accepted as a validated instrument to support the diagnostic concept (de Meyer et al, 2010;Dubois et al, 2010;Dubois et al, 2007;Gauthier et al, 2008). Alois Alzheimer first described the hallmarks of AD with plaques and neurofibrillary tangles (NFT) more than a hundred years ago.…”
Section: Definition and Epidemiology Of Rapidly Progressive Admentioning
confidence: 99%